Philosophical Thoughts of Ibn Miskawaih - Mohammad Abdul Al Halib; Dadang Zenal Mutaqin; Rizki Abdul Basir; Fajar Solihin; Siti Hanna Nur Asyiah (Penerbit Hellow Pustaka, 2025)
Ibn Maskawaih, a Muslim philosopher who was active in the 10th century, greatly influenced the development of ethical and psychological thought in the tradition of Islamic philosophy. His thoughts that touch on various fields, including ethics, morality, and soul development, bring a new perspective in understanding the relationship between ratio, emotions, and human actions. This article aims to analyze Ibn Maskawaih's main contributions to Islamic philosophy, by highlighting his key concepts, such as happiness, the ethics of virtue, and the spiritual journey of man.